2016
DOI: 10.1530/edm-15-0118
|View full text |Cite
|
Sign up to set email alerts
|

A case of adrenal Cushing’s syndrome with bilateral adrenal masses

Abstract: SummaryA functional lesion in corticotrophin (ACTH)-independent Cushing’s syndrome is difficult to distinguish from lesions of bilateral adrenal masses. Methods for distinguishing these lesions include adrenal venous sampling and 131I-6β-iodomethyl-19-norcholesterol (131I-NP-59) scintigraphy. We present a case of a 29-year-old Han Chinese female patient with a history of hypercholesterolaemia and polycystic ovary syndrome. She presented with a 6month history of an 8kg body weight gain and gradual rounding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…When the recurrence occurred, the contralateral adrenal gland was also removed. Such an approach is justified by other studies, and our results correlate with those indicating that, in the long-term, recurrence of hypercortisolaemia after unilateral adrenalectomy is seen in approximately 20% of patients [11,12].…”
Section: Discussionsupporting
confidence: 86%
“…When the recurrence occurred, the contralateral adrenal gland was also removed. Such an approach is justified by other studies, and our results correlate with those indicating that, in the long-term, recurrence of hypercortisolaemia after unilateral adrenalectomy is seen in approximately 20% of patients [11,12].…”
Section: Discussionsupporting
confidence: 86%
“…In this case, we used the AV: IVC aldosterone ratio to assess the successfulness of catheter insertion since the aldosterone concentration could remain stable during the sampling. There were some researches in which adrenaline concentration was measured to evaluate catheterization accuracy, however, catheterization process itself might lead to stress-induced fluctuation of adrenaline and further result in misjudgment [ 17 , 34 ]. Even though there is still no general agreement on the definition of catheterization success in AVS, aldosterone concentration instead of adrenaline could be a robust assay for this purpose, after the aldosterone overproduction being excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although early 75 Se-selenomethyl-19-norcholesterol studies showed promising results, scintadren is currently no longer available for clinical studies and has been replaced by 131 I-iodomethyl-norcholesterol (NP-59) [25]. In a declining number of cases, NP-59 continues to be used to investigate the secretory status of adrenal adenomas and aid lesion lateralization [26,27,28,29,30,31]. However, these techniques have significant shortcomings including delivery of a relatively high radiation dose to the adrenal glands, time-consuming acquisition protocols, a requirement for the patient to take a 7–10 day course of high-dose glucocorticoids to suppress non-autonomous hormone synthesis and low sensitivity with poor spatial resolution (traditionally only allowing reliable detection of lesions >2 cm in diameter, although single photon emission computed tomography (SPECT) may afford improved resolution).…”
Section: Norcholesterol Scintigraphy—historical Perspectivementioning
confidence: 99%